A Case of Vaping TCH Oil Leading to Vaping Associated Pulmonary Injury: Our Approach to Its Diagnosis, Management, and Recommendations. (5th January 2020) - Singh, Anshika; Tan, Qiuxue; Saccone, Nicole M.; Lindner, David H.
Abstract : Vaping's popularity has grown exponentially since its introduction to the US market in 2003. Its use has sky-rocketed since the unveiling of the vaping pods in 2017 which may account for the advent of the vaping related illnesses we are now seeing. Substances such as nicotine solution, tetrahydrocannabinol (THC) oil, cannabidiol (CBD) oil, and butane hash oil (BHC) packaged in cartridges available in various flavors and concentrations are aerosolized by the heating of metal coils in the e-cigarette/vaping devices. Cases from all over the country have recently been coming to light in which vaping has led to severe acute pulmonary disease or vaping-associated-pulmonary-injury (VAPI). A vast majority of the presenting patients in the reported cases have required hospitalization and intensive care, needing supplemental oxygen and even endotracheal intubation and mechanical ventilation. 98% of patients present with respiratory symptoms (dyspnea, hypoxia, chest pain, cough, hemoptysis), 81% of patients have gastrointestinal symptoms (nausea, vomiting, diarrhea, and abdominal pain), and 100% of patients have constitutional symptoms such as fever, chills, and fatigue/malaise on presentation. Although based on history and clinical presentation it is reasonable to have a high suspicion for VAPI, diagnostic workup to rule out alternative underlying causes such as infection, malignancy, or autoimmune process should be performed before establishing the diagnosis. Computed Tomography (CT) scans of the chest have predominantly shown ground-glass opacity in the lungs, often with areas of lobular or subpleural sparing. Although lung biopsies have been performed on a relatively low number of cases, lung injury patterns so far have shown acute fibrinous pneumonitis, diffuse alveolar hemorrhage, or organizing pneumonia, usually bronchiolocentric, and accompanied by bronchiolitis. Treatment plans that have led to clinical improvement in the reported cases center around high-dose systemic steroids, although there are a lack of data regarding the best regimen and the absolute need for corticosteroids. The role of antibiotics appears to be limited once infection has definitively been ruled out. We present the case of a young male who vaped THC oil and developed severe acute pulmonary injury requiring mechanical ventilation and showed a remarkable response to high dose steroid therapy with improvement in clinical symptoms and resolution of diffuse ground glass opacity on repeat HRCT scan.